PENCEGAHAN PERLUASAN KASUS SCABIES DENGAN PENDEKATAN PERAWATAN TERKINI DI BOARDING SCHOOL : PENCEGAHAN PERLUASAN KASUS SCABIES DENGAN PENDEKATAN PERAWATAN TERKINI DI BOARDING SCHOOL - shindi hapsari; Eni Kusyati (Open Edutech Indonesia, 2023)
Scabies disease is an itchy disease of the skin, caused by density, moisture, and neglect of personal hygiene. Living together with a group of people such as in Islamic boarding schools is at risk of easily contracting various skin diseases, especially scabies. Attention to issues to improve health status, especially in student groups in boarding schools or boarding schools is a promotive and preventive effort. This service activity aims to determine the description of personal hygiene behavior and the environment of students in the boarding school area. The method of this activity is descriptive and observational. The population of this activity is students of Bina Amal Junior High School boarding school with a sample of 138 students. Activities are carried out by preparing survey links to data on the incidence of scabies, sources of spread, understanding of scabies, and management of scabies either prevention or after it occurs. Then it is carried out by providing education about the concept of scabies and procedures for clean living behavior in schools to demonstrations of wound care for scabies cases. The results of this activity showed that there was a change in student behavior to maintain the cleanliness of the environment